Cocoa production with geographical indication gi in the region of linhares/es: Aspects of governance and quality - Neto, Euclides Teixeira; Pigatto, Giuliana Aparecida Santini [UNESP]; Lourenzani, Ana Elisa Bressan Smith [UNESP] (My University, 2018)
The objective was to analyze the governance structure established between the producers and buyers of cocoa - after obtaining the geographical indication (GI) in the production of the Linhares/ES region, and verifying if it brings greater efficiency in the transaction and coordination. The methodological procedures involved documentary analysis (related to the registration and regulation of production with GI in the Linhares region) and case studies with cocoa producers within the scope of the Association of Cocoa Growers Linhares (ACAL). The instrument used was the form, applied through semi-structured interviews with producers in the year 2016. The results showed that the relationship of governance established between producers and buyers agents of cocoa - after obtaining the geographical indication - has not allowed greater efficiency in the transaction and coordination, since the products involved cannot be traded with the GI registry, which refers to the exchange of information between agents, specific quality demands, which could refer to hybrid governance structures.
Produção de cacau com indicação geográfica (Ig) na região de linhares/es: aspectos de governança e qualidade
Keywords: Cocoa; Governance; Quality